THE EFFECTS OF CELEBRITY ENDORSEMENT, CELEBRITY ATTRIBUTES, BRAND IMAGE AND E-WOM ON PURCHASE DECISIONS THROUGH INSTAGRAM - Tri Hendro Sigit Prakoso; Vicky Nathasya (Universitas Sarjanawiyata Tamansiswa, 2022)
Indonesia has significant social media users globally. One of the most popular social media in Indonesia is Instagram. Through Instagram,companies can do marketing with celebrities as an endorser. Celebrity endorsements attract consumers' attention and encourage consumers into purchasing decisions. Consumer perception of a celebrity is determined by his or her attractiveness, expertise and credibility. Another factor that affects consumer purchasing decisions is the brand image. Nowadays, plenty of companies are using Instagram to build consumer assurance. Consumers also avail themselves to Instagram to provide reviews on products so that it may be taken into account byother consumers to purchase these products. This phenomenon defines as E-WOM (Electronic Word of Mouth). This study aims to determine the effect of celebrity endorsement, celebrity attributes, brand image and E-WOM on purchasing decisions through Instagram . With 298 respondents, data were collected through Google Forms SPSS 26 for the Mac used to analyze these data using the multiple regression analysis techniques. This research showed that celebrity endorsement, celebrity attributes, brand image, and E-WOM positively and significantly affected purchasing decisions through Instagram.